Mycobacterium gordonae (Actinomycetota: Mycobacteriales: Mycobacteriaceae) Infecting Captive‐Reared Laurel Dace, Chrosomus saylori (Cypriniformes: Leuciscidae) in North America - Daniel Gordillo‐González; Steven P. Ksepka; Haley R. Dutton; Kamila Cajiao‐Mora; John H. Brule; Bernard R. Kuhajda; Anna L. George; Stephen A. Bullard (Journal of Fish Diseases, 2026)
A captive‐reared cohort of Laurel Dace, Chrosomus saylori (Skelton 2001) (Cypriniformes: Leuciscidae), a federally‐endangered species endemic to several streams in eastern Tennessee's Cumberland Plateau, exhibited signs of morbidity and trickling mortalities in a recirculating aquaculture system. Ziehl‐Neelsen (ZN) staining revealed acid‐fast rod‐shaped bacteria within necrotic and intracellular lesions affecting the eye, swim bladder, spleen, and ovary. Histopathology showed granulomatous inflammation characterised by macrophages, multinucleated giant cells, and eosinophilic exudates. The eye, swim bladder, and ovary were particularly impacted: the choroid plexus of the eye displayed haemorrhages and dense cellular infiltrates; the swim bladder exhibited granulomatous inflammation with extensive fibrosis; the ovary contained caseous granulomas; and the choroid plexus of the eye displayed haemorrhages and dense cellular infiltrates. PCR amplification of the hsp65 gene (316 bp) from formalin‐fixed and paraffin‐embedded lesioned tissues was identical (100% similar; 424 bp fragment) to that of the type strain of Mycobacterium gordonae Bojalil et al. 1962 (AF547840). This is the first report of an infection by M. gordonae in Laurel Dace; the first record of this bacterium causing a lesion in the swim bladder, eye, or ovary; and the first record of M. gordonae from a freshwater fish in North America.

Freeze Tolerance of Amyloodinium ocellatum (Myzozoa: Blastodiniales) - Robert D. Gonzales; Haley R. Dutton; Reginald B. Blaylock; Stephen A. Bullard; Eric A. Saillant (Journal of Fish Diseases, 2026)
Amyloodinium ocellatum causes epizootics in marine fish hatcheries. Frozen, wild fish, often used as food in aquaculture, could introduce the disease. We investigated the parasite's ability to survive, reproduce and infect a host after freezing. Infected gills were frozen at −20°C for either 0, 24, 36, 48, or 72 h. Parasite viability was assessed first by placing thawed infected gills into tanks with naïve fish. Gills of the exposed fish were examined on day 0 and on days 4 and 7 post‐exposure. Tomonts from infected gills in all freeze durations produced infections. However, dinospore production decreased and infections took longer to establish in fish exposed to tomonts from the 72 h treatment. Second, eight tomonts from each freeze duration were placed in 5 mL of 25 ppt artificial seawater at 22°C in individual wells of a 12‐well plate and monitored for hatching. Ninety seven percent of tomonts from all treatments hatched. Tomonts frozen for up to 72 h survived, reproduced and infected fish, but dinospore production decreased as freeze duration increased. Extrapolation from the rate of reduction in dinospore production over the freeze durations tested suggests that a freeze duration of 237 h could inactivate all tomonts.

Catadiscus marielaosornae n. sp. (Digenea: Diplodiscidae) infecting the intestine of Peters’ thin-toed frog, Leptodactylus petersii (Steindachner) (Anura: Leptodactylidae) from the Yahuarcaca Lake System, Amazon River (Leticia, Colombia), with phylogenetic analysis - Kamila Cajiao-Mora; José Rancés Caicedo-Portilla; John H. Brule; Haley R. Dutton; Stephen A. Bullard (Systematic Parasitology, 2025)
We describe Catadiscus marielaosornae Cajiao-Mora and Bullard n. sp . (Diplodiscidae) from the intestine of Peters’ thin-toed frog, Leptodactylus petersii (Steindachner) (Anura: Leptodactylidae) from the Yahuarcaca Lake System, Colombia. We assigned our specimens to Catadiscus Cohn, 1904 because they have a smooth-surfaced, pyriform body, centrally-constricted ventro-terminal acetabulum that lacks an accessory sucker, pharynx with extramural sacs, oesophageal bulb, and single testis. The new species differs from all but Catadiscus rodriguezi Caballero, 1955, Catadiscus marinholutzi Freitas and Lent, 1939, and Catadiscus propinquus Freitas and Dobbin, 1956 by having a vitellarium that is confluent anteriorly ( vs . two non-confluent fields). It differs from the aforenamed congeners by having a ventral common genital pore that opens anterodextral to the oesophageal bifurcation, round vitelline follicles that become confluent anterior to the testis, and a 1: 2–3 ratio of acetabulum: testis width. Our 28S phylogenetic analysis recovered the new species sister to C. marinholutzi , and Diplodiscidae as paraphyletic, with Catadiscus sister to a clade comprising a sequence ascribed to Chiorchis fabaceus (Diesing, 1838) Fischoeder, 1901 (Cladorchiidae), and sequences of three species of Diplodiscus Diesing, 1836. The species description herein includes several features pertaining to the acetabulum, female genitalia, and excretory system that could comprise useful character states with which to more readily classify and diagnose diplodiscid species and genera. To our knowledge, this is the first record of a digenean infecting Peters’ thin-toed frog, and it is also the first record of any parasite infecting any ditch frog ( Leptodactylus spp.) from Colombia.

Resurrection and emendation of Pseudoparamacroderoides Gupta & Agrawal, 1968 (Digenea: Macroderoididae), description of a new species from Vietnam, and comments on the systematics of macroderoidid genera - Triet N. Truong; Stephen S. Curran; Haley R. Dutton; Stephen A. Bullard (Systematic Parasitology, 2021)

A new species and emendation of the seldom reported Enterohaematotrema Mehra, 1940 (Digenea: Schistosomatoidea), including a revised phylogenetic hypothesis for turtle blood flukes - Haley R. Dutton; Stephen A. Bullard (Systematic Parasitology, 2020)

An updated geographic distribution of Myxobolus cerebralis (Hofer, 1903) (Bivalvulida: Myxobolidae) and the first diagnosed case of whirling disease in wild‐caught trout in the south‐eastern United States - Steven P. Ksepka; Jacob M. Rash; Brandon L. Simcox; Doug A. Besler; Haley R. Dutton; Micah B. Warren; Stephen A. Bullard (Journal of Fish Diseases, 2020)
Myxobolus cerebralis (Bivalvulida: Myxobolidae), the aetiological agent of salmonid whirling disease, was detected in 2 river basins of North Carolina during 2015, which initiated the largest spatial–temporal monitoring project for the disease ever conducted within the south‐eastern United States (focused mainly in eastern Tennessee and western North Carolina). A total of 2072 rainbow trout Oncorhynchus mykiss , 1,004 brown trout Salmo trutta and 468 brook trout Salvelinus fontinalis were screened from 113 localities within 7 river basins during June 2017 through October 2019. Infections were detected by pepsin–trypsin digest, microscopy and the species‐specific nested polymerase chain reaction (PCR) in 19 localities across 6 river basins. Myxospore morphology was indistinguishable from the published literature. In 2019, five rainbow trout that symptomatic for whirling disease (sloping neurocranium and lordosis) were captured and processed for histopathology. Myxospores were detected in the calvarial cartilage of two deformed trout with associated erosion of the cartilage consistent with reported whirling disease lesions. This is the first report of M. cerebralis in Tennessee and the first histologically confirmed cases of whirling disease in southern Appalachian (south‐eastern United States) rivers and streams and expands the distribution of M. cerebralis throughout western North Carolina and eastern Tennessee.